Mycosporine-Like Amino Acids and Their Derivatives as Natural Antioxidants - Naoki Wada; Toshio Sakamoto; Seiichi Matsugo (MDPI AG, 2015)
Mycosporine-like amino acids (MAAs) are water-soluble molecules that absorb UV-A and UV-B radiation and disperse the energy as heat. MAAs show great diversity in their molecular structures, which exhibit a range of molecular weights spanning 188 to 1050 Daltons. MAAs are utilized in a wide variety of organisms including prokaryotes and eukaryotic micro-organisms that inhabit aquatic, terrestrial, and marine environments. These features suggest that MAAs are stable and fundamental molecules that allow these organisms to live under UV irradiation. MAAs are thought to have been greatly important to ancient forms of life on Earth, functioning as a primary sunscreen to reduce short-wavelength light. Structurally different MAAs might have been developed in MAA-producing organisms during their environmental adaptation. Harmful irradiation directly damages biomolecules, including lipids, proteins and DNA, and induces oxidative stress through radical-propagating processes. Thus, MAAs are expected to play an additional role in the antioxidant system. This review focuses on MAAs with radical scavenging activities. To cover all the reported MAAs known thus far, we surveyed the CAS database and have summarized the structures and the chemical and physical properties of these MAAs, including their antioxidant activities.